Combating the COVID-19 infodemic: a three-level approach for low and middle-income countries - Dash, Sambit; Parray, Ateeb Ahmad; De Freitas, Loren; Mithu, Md Imran Hossain; Rahman, Md Mustafizur; Ramasamy, Aarthy; Pandya, Apurva Kumar (BMJ Journals, 2022)
This article was published in BMJ Global Health by BMJ Journals [© Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2020-004671 The Journal's website is at: https://gh.bmj.com/content/6/1/e004671